Effect of Professional Ownership on Compassion Fatigue and Quality of Life among Midwives - İpek Turan; Hacer Ünver Koca (Artuklu Health)

(untitled)
Introduction: This study aims to examine the effect of professional belonging on compassion fatigue and quality of life among midwives.Methods: This relational descriptive study was conducted with 410 midwives working in 1st and 2nd level health institutions in Malatya province between 01.03.2020 and 15.07.2021. Data were collected using a web-based survey sent online. Data were collected using the Personal Introduction Form, Midwifery Belonging Scale, Compassion Fatigue Brief Scale, and Quality of Life Scale for Employees.Results: The average age of the midwives in the study was 33.02, 76.6% had a bachelor's degree, 62.4% were married, 46.8% had an income equal to their expenses, 50.0% did not have children, 90.7% did not find the salary they received as a midwife sufficient, 58.3% chose the midwifery profession in order not to have problems finding a job, 30.7% were currently working at ASM, 89.8% did not have an administrative position at the institution, 48.5% worked in shifts, and the average total service period was 9.08%. A statistically significant relationship was found between the midwives' professional sense of belonging total mean score (75.99 ± 18.94) and the quality of life sub-dimension burnout (23.23 ± 5.89) at a low level negatively, and a moderately positive relationship with professional satisfaction (28.91 ± 10.06) (p<0.001). In addition, it was determined that professional satisfaction among midwives had a statistical significance of 20% in explaining midwifery affiliation (p˂0.001), while burnout had a statistical significance of 8% in explaining midwifery affiliation (p˂0.05).Conclusion: This study found that the burnout sub-scale of professional quality of life decreased and professional satisfaction increased with the increase in professional belonging among midwives. The important to emphasize the concepts of burnout and professional satisfaction and to follow institutional policies about this issue to increase professional belonging among midwives.